2016
DOI: 10.1007/s10800-016-0976-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrocatalytic performance of phosphotungstic acid-modified Ag@Pt/MWCNTs catalysts for oxygen reduction reaction

Abstract: Keggin-structured phosphotungstic acid H 3 PW 12 O 40 (HPW)-modified Ag@Pt/MWCNTs electrocatalysts were successfully prepared using a chemical impregnation method. Physical characterization by X-ray powder diffraction, high-resolution transmission electron microscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy revealed that the HPW molecules were incorporated into the Ag@Pt/MWCNT structure The diameter of the catalyst used was about 4.0 nm, and electrochemical investigation results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…More recently, a PW 12 -modified Ag@Pt/MWCNT electrocatalyst was prepared by electrostatic interaction with positively charged chitosan-functionalized core-shell Ag@Pt NPs on MWCNTs. 261 The results showed that PW 12 improves the electrocatalytic activity of Ag@Pt NPs; with a E 1/2 (half-wave electrode potential) for the ORR which positively shifted 44 mV from that of Ag@Pt NPs/MWCNTs, and a mass activity (I m ) and specific area activity (I s ) about 2 times higher than those of Ag@Pt NPs/MWCNTs. The enhanced activity can be explained by the protective effect of the PW 12 layer on the catalyst surface.…”
Section: Poms As Co-catalysts For Orrmentioning
confidence: 93%
“…More recently, a PW 12 -modified Ag@Pt/MWCNT electrocatalyst was prepared by electrostatic interaction with positively charged chitosan-functionalized core-shell Ag@Pt NPs on MWCNTs. 261 The results showed that PW 12 improves the electrocatalytic activity of Ag@Pt NPs; with a E 1/2 (half-wave electrode potential) for the ORR which positively shifted 44 mV from that of Ag@Pt NPs/MWCNTs, and a mass activity (I m ) and specific area activity (I s ) about 2 times higher than those of Ag@Pt NPs/MWCNTs. The enhanced activity can be explained by the protective effect of the PW 12 layer on the catalyst surface.…”
Section: Poms As Co-catalysts For Orrmentioning
confidence: 93%
“…For instance, a variety of supporting materials including foam silica, multiwalled carbon nanotubes (MWNTs), and indium tin oxide (ITO) have been utilized to support the nanocatalysts. However, reduced graphene oxide (RGO) has been used as a catalyst support for DAFCs due to the large specific surface area, superior electric conductivity, and high chemical stability. , Recently, heteropolyacids (HPAs) have also been incorporated into the bimetals to improve the catalytic performance. , HPAs are a rapidly increasing class of compounds and have been extensively studied as catalysts, additives, chemical cleaners, and surface promoters, owing to their unique structural and electronic versatility, in which phosphotungstic acid (H 3 PW 12 O 40 , HPW) is one of the most investigated Keggin-type HPAs. A most appealing and notable characteristic of HPW is that they can acquire and release several electrons per molecule without changing the structure. , …”
Section: Introductionmentioning
confidence: 99%
“…23,24 Recently, heteropolyacids (HPAs) have also been incorporated into the bimetals to improve the catalytic performance. 25,26 HPAs are a rapidly increasing class of compounds and have been extensively studied as catalysts, additives, chemical cleaners, and surface promoters, owing to their unique structural and electronic versatility, 27 HPW is that they can acquire and release several electrons per molecule without changing the structure. 28,29 Herein, phosphotungstic acid and PdNi nanoparticles supported on RGO (PdNi/RGO/HPW) nanomaterials were simply synthesized by a facile chemical method, in which PdNi/ RGO nanomaterials were first synthesized, followed by the subsequent introduction of HPW into the composite in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%